Oral, Maxillofacial and Dental Diseases in Captive Cheetahs (Acinonyx jubatus). Issue 1 (January 2018) - Steenkamp, G.; Boy, S.C.; van Staden, P.J.; Bester, M.N.
Summary: Descriptions of several oral, maxillofacial and dental conditions/diseases exist for a variety of captive large felids, but little is reported on the pathology of free roaming large felids. Apart from focal palatine erosions (FPEs) as initially described by Fitch and Fagan (1982) and some reference to absent incisor teeth, few data exist on diseases affecting the oral, maxillofacial and dental structures of cheetahs ( Acinonyx jubatus ), regardless of their captivity status. This study reports 18 different conditions affecting the teeth, bone and oral cavity soft tissue of cheetahs, based on initial assessment of 256 animals over 11 years (2002–2012) in South Africa and Namibia. This report excludes oral tumours or FPEs, but includes several acquired and developmental conditions never described before.